EXAMINING THE CORRELATION BETWEEN INTRINSIC READING MOTIVATION ON READING SKILLS IMPROVEMENT - Adinugraha, Danang Wasana; Arifani, Yudhi; Assassi, Tarek (Indonesian Teaching English to Speakers of Other Languages Journal, 2024)
This study examines the correlation between intrinsic reading motivation and the improvement of reading skills among college students. It investigates how intrinsic motivation—driven by factors such as curiosity, enjoyment, and the challenge of complex texts—affects students' reading abilities over time. The study also compares intrinsic motivation levels between male and female students and identifies key factors that contribute to reading improvement. Previous research on intrinsic motivation in reading has often lacked a detailed categorization of motivation levels (low, medium, high). The current research fills this gap using a quantitative approach, involving a sample of 47 students (9 males and 38 females) from the first and third semesters of an English program. The instruments used for data collection include a questionnaire adapted from Guthrie and Wang (2004) and a TOEFL-based reading test. The results indicate that intrinsic motivation significantly correlates with reading skill improvement, with a Pearson correlation of 0.644 (p > 0.05), suggesting a moderate to strong positive relationship. Gender differences in motivation were observed, with males scoring a mean of 8.56 (SD = 1.23) and females scoring a mean of 9.29 (SD = 2.19) on the intrinsic motivation scale. A t-test revealed a non-significant difference in motivation levels between genders (p = 0.341). The analysis also identified that factors like curiosity, challenge, and involvement play a crucial role in reading improvement, with involvement being the most influential factor (r = 0.937). These findings highlight the importance of intrinsic motivation in enhancing reading skills and suggest that educators should foster motivation by focusing on these key factors. Future research should incorporate extrinsic motivation and consider a larger, more diverse sample to provide further insights.